Rare earth stibolyl and bismolyl sandwich complexes - Schwarz, Noah; Bruder, Florian; Bayer, Valentin; Moreno-Pineda, Eufemio; Gillhuber, Sebastian; Sun, Xiaofei; van Slageren, Joris; Weigend, Florian; Roesky, Peter W. (Nature communications, 2025)
The design of molecular rare earth complexes to achieve unique magnetic and bonding properties is a growing area of research with possible applications in advanced materials and molecular magnetics. Recent efforts focus on developing ligand frameworks that can enhance magnetic characteristics. Here we show the synthesis and characterization of a class of rare earth complexes, [(η 5 -C 4 R 4 Sb)Ln(η 8 -C 8 H 8 )] and [(η 5 -C 4 R 4 Bi)Ln(η 8 -C 8 H 8 )], featuring η 5 -coordinated stibolyl and bismolyl ligands. The ligand aromaticity and bonding situation within these complexes are investigated by quantum chemical calculations. Magnetic studies of the Er III analogues reveal large barriers and intriguing properties, including waist-restricted hysteresis and slow relaxation of the magnetization, making them single-molecule magnets. Comparison between the experimental barrier and CASSCF-SO calculations indicates that relaxation in all systems occurs through high-energy excited states. These findings suggest that stibolyl and bismolyl ligands can be promising candidates for achieving high-energy barriers in Er-based SMMs, offering a pathway to molecular designs with enhanced magnetic properties. Cyclopentadienyl ligands are central to organometallic lanthanide chemistry as their electron-donating ability enables fine-tuning for various applications including catalysis, luminescent materials, and single molecule magnets. Here, the authors report the synthesis and characterization of the lanthanide complexes featuring η 5 -coordinating heterocyclic stibolyl and bismolyl ligands.